2014
DOI: 10.1371/journal.pone.0103827
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Decay Factor AUF1 Binds the Internal Ribosomal Entry Site of Enterovirus 71 and Inhibits Virus Replication

Abstract: AU-rich element binding factor 1 (AUF1) has a role in the replication cycles of different viruses. Here we demonstrate that AUF1 binds the internal ribosome entry site (IRES) of enterovirus 71 (EV71) and negatively regulates IRES-dependent translation. During EV71 infection, AUF1 accumulates in the cytoplasm where viral replication occurs, whereas AUF1 localizes predominantly in the nucleus in mock-infected cells. AUF1 knockdown in infected cells increases IRES activity and synthesis of viral proteins. Taken t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
93
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(100 citation statements)
references
References 46 publications
4
93
3
Order By: Relevance
“…By binding to defined genomic elements and by modulating viral protein or RNA synthesis, AUF1/hnRNPD was found to accelerate or inhibit the life cycles of various RNA viruses (Paek et al 2008;Lund et al 2012;Cathcart et al 2013;Hino et al 2013;Lin et al 2014). It is quite conceivable that the methylation-enhanced RNA restructuring activity of the AUF1 p45 isoform, which was demonstrated here to support WNV replication, may underlie several of the functions of AUF1 during the replication processes of other viruses as well.…”
Section: Discussionmentioning
confidence: 67%
“…By binding to defined genomic elements and by modulating viral protein or RNA synthesis, AUF1/hnRNPD was found to accelerate or inhibit the life cycles of various RNA viruses (Paek et al 2008;Lund et al 2012;Cathcart et al 2013;Hino et al 2013;Lin et al 2014). It is quite conceivable that the methylation-enhanced RNA restructuring activity of the AUF1 p45 isoform, which was demonstrated here to support WNV replication, may underlie several of the functions of AUF1 during the replication processes of other viruses as well.…”
Section: Discussionmentioning
confidence: 67%
“…Among them, several members of the hnRNPs family have been previously shown to play a role in regulating viral replication. 7,8,39,[44][45][46][47] For examples, hnRNP C and K were documented to interact with the non-coding regions of enteroviral RNA to facilitate translation initiation and RNA synthesis. 44,45,47 Similar to our findings in the current study, enteroviral infection causes cytoplasmic redistribution and cleavage of hnRNP D and deletion of this protein results in enhanced viral replication, suggesting that hnRNA D acts as a host restriction factor against enterovirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…44,45,47 Similar to our findings in the current study, enteroviral infection causes cytoplasmic redistribution and cleavage of hnRNP D and deletion of this protein results in enhanced viral replication, suggesting that hnRNA D acts as a host restriction factor against enterovirus infection. 7,8,39 The antiviral mechanisms of hnRNP D appear to involve negative regulation of internal ribosome entry site (IRES)-mediated translation of viral RNA via direct interaction with the IRES of enteroviruses, 7,46 and viral RNA degradation by targeting the 3′-untranslated region (UTR) of enteroviral genome. 39 The exact mechanism of TDP-43 suppressing CVB3 replication remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Pairing PAR-CLIP with RNA-seq and polysome analysis following AUF1 overexpression implicated AUF1 in a range of regulatory events including stabilization and destabilization of both mRNA and ncRNA, promotion and repression of translation, and modulation of alternative splicing. In addition, AUF1 has recently been shown to have a role in the life cycle of DNA and RNA viruses including Epstein-Barr virus [123,124], HIV [125], hepatitis C virus [126], West Nile virus [127,128], and several picornaviruses [129,130,131,132]. …”
Section: Adenylate Uridylate-rich Element (Are)-mediated Mrna Decamentioning
confidence: 99%
“…This finding was later expanded to include binding to HRV, CVB3, and EV71 RNA [129,132,133]. It was subsequently discovered that AUF1 knockout or knockdown in human or mouse cells resulted in increased replication of these viruses, suggesting that AUF1 may act as a host restriction factor to EV infection [129,130,131,132]. Prior to these discoveries, a study of HRV-16 infection of human airway epithelial cells reported the observation that cytoplasmic levels of AUF1 increased during infection [134].…”
Section: Adenylate Uridylate-rich Element (Are)-mediated Mrna Decamentioning
confidence: 99%